Environmentally improved CdTe photovoltaic recycling through novel technologies and facility location strategies. (8th June 2020) - Ravikumar, Dwarakanath; Seager, Thomas; Sinha, Parikhit; Fraser, Matthew P.; Reed, Serrae; Harmon, Elise; Power, Alexis
Abstract: Photovoltaic waste is projected to reach up to 78 million tons across globally dispersed locations through 2050. Current recycling infrastructure is inadequate to process these waste volumes responsibly. This necessitates commercializing novel, environmentally advantageous photovoltaic recycling technologies that improve upon incumbent industrial operations. CdTe photovoltaic recycling is a promising candidate for improvements as 25, 000 tons of spent modules are recycled worldwide annually. This paper evaluates the operational performance and compares six novel technologies, the incumbent technology used in industry and one technology which extends the incumbent process across ten environmental impact categories. The tradeoff between incurring a transportation burden (ship or road) to recycle in a large‐scale centralized facility with a higher operational efficiency and avoiding transportation by recycling in a small‐scale decentralized facility with a lower operational efficiency is evaluated. Thermal delamination to eliminate the ethylene vinyl acetate and separate the photovoltaic glass panels is preferable to the incumbent mechanical process across nine environmental impact categories and decreases the climate‐change impact of CdTe photovoltaic recycling by 23%. Bath and probe sonication are ineffective for delamination, and the use of organic solvents is more environmentally burdensome than the incumbent mechanical process. Centralized recycling with shipping is environmentally preferable than with road‐based transportation. For every 100‐km increase in road transportation from the decentralized to the centralized facility, the inventory requirement in the centralized facility should be 6% lower than the decentralized facility for centralized recycling to have a lower climate‐change impact than decentralized recycling. The corresponding value for shipping is 0.4%. Abstract : Eight novel CdTe photovoltaic recycling technologies were compared with the incumbent used in industry and a literature‐reported technology. Thermal delamination with precipitation of cadmium and tellurium has a 23% lower climate‐change impact than the incumbent used in industry. In removing ethylene‐vinyl acetate, sonication was ineffective and using organic solvents was environmentally burdensome. A 100‐km increment in road transportation necessitates a 6% reduction in inventory at the centralized facility for centralized recycling to have a lower climate‐change impact than decentralized recycling.